Níveis de inclusão de silagem de bagaço de uva na dieta de cordeiros em fase de terminação - Maciel, Marcus Brocardo (2012)
The present study aimed to evaluate the performance, carcass characteristics, the fatty acid profile and meat quality of lambs fed increasing levels of grape pomace silage replacing alfalfa. We used 24 not castrated Texel lambs, with an average weight of 24.5 kg and a mean age of 100 days, randomly distributed in a completely randomized design with four treatments and six replications. The treatments consisted of increasing levels of grape pomace silage (SBU) of 0%, 15%, 30% and 50% on a full ration. Observed effect of inclusion level of SBU consumption of dry matter, crude protein, total digestible nutrients (P <0.01) decreased as the inclusion level of SBU increased. A quadratic effect of inclusion levels of SBU on consumption of lipids (CEE) (P <0.01) was observed. The use of neutral detergent fiber and feed conversion was not affected by inclusion level of dietary SBU. The inclusion level of SBU in the diets affected (P <0.01) the average daily weight gain, which decreased with increasing dietetic SBU, presenting average values of 268, 251, 235 and 213g for levels: 0 , 15, 30 and 50% of SBU inclusion in the diet, respectively. There was no effect (P> 0.05) in the level of inclusion of SBU carcass characteristics, weights of body components and weights and proportions of commercial cuts of lambs. It was observed (P <0.01) that the level of inclusion of SBU has promoted an increasing of linoleic acid (C18: 2n6c) concentration in Longissimus dorsi muscle. It was also observed increase in the content of polyunsaturated fatty acids (P <0.05). Moreover, the ratio between polyunsaturated fatty acids to saturated (P: S) was improved to values of 0.179, 0.192, 0.226 and 0.227 (P <0,05), respectively as the SBU was increased. However, the increase of SBU promoted increasing (P <0.01) of the content of omega 6 (n-6) in relation to the content of omega 3 (n6: n3) presenting ratios of 3.16, 4.85, 6.39, 6.82, respectively for levels of 0, 15, 30 and 50% of SBU tested. The softness, cholesterol, pH and chemical composition of muscle tissue were not affected (P> 0.05) by the level of SBU. As a result, it can be concluded that the grape pomace silage is an alternative source of nutrients for lambs and can be used as a substitute for good quality hay, for providing satisfactory performance, without carcass characteristics and body components alteration, producing a healthier meat for human consumption due to the increase of polyunsaturated fatty acids content.